TALENT ACQUISITION, EMPLOYEE ENGAGEMENT, PRODUKTIVITAS KARYAWAN, PELATIHAN PENGEMBANGAN, KOMPENSASI, DAN REWARD PADA PROFITABILITAS PERUSAHAAN STARUP - Pretty Failasufa Aziza; Sugito (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to analyze the influence of talent acquisition, employee engagement, employee productivity, training and development, compensation, and reward on company profitability in the Indonesian startup sector. This study employs a quantitative method with an associative approach. Primary data were collected through questionnaires distributed to employees and managers of startup companies. The sample consisted of 100 respondents selected through purposive sampling. Data analysis was conducted using descriptive statistics and multiple linear regression with the assistance of SPSS.The findings indicate that talent acquisition, employee engagement, employee productivity, training and development, compensation, and reward simultaneously and partially have a significant influence on company profitability, with employee productivity and compensation being the most dominant variables. The implications of this study suggest that investment in human resources should be regarded as a strategic asset that directly contributes to the firm's financial performance, requiring synergy between the human resource management function and the accounting function in corporate planning and performance measurement